Consumer behavior and culture : consequences for global marketing and advertising - Mooij, Marieke K. de (SAGE, 2004)
De Mooij argues that differences in consumer behaviour across countries are not decreasing, but increasing. This book provides empirical evidence that the need to understand culture to explian differences in consumer behaviour is greater than ever.